2016
DOI: 10.1371/journal.pone.0147349
|View full text |Cite
|
Sign up to set email alerts
|

Association of Right Ventricular Pressure and Volume Overload with Non-Ischemic Septal Fibrosis on Cardiac Magnetic Resonance

Abstract: BackgroundNon-ischemic fibrosis (NIF) on cardiac magnetic resonance (CMR) has been linked to poor prognosis, but its association with adverse right ventricular (RV) remodeling is unknown. This study examined a broad cohort of patients with RV dysfunction, so as to identify relationships between NIF and RV remodeling indices, including RV pressure load, volume and wall stress.Methods and ResultsThe population comprised patients with RV dysfunction (EF<50%) undergoing CMR and transthoracic echo within a 14 day (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
10
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 25 publications
0
10
0
Order By: Relevance
“…Among these patients, 90% (n=246) were accrued prospectively as part of NIH protocols utilizing CMR and echo for CAD associated remodeling (NIH 1R01HL128278-01, K23 HL102249-01) [14], and 10% were accrued via a retrospective registry of patients with chronic obstructive CAD as verified by invasive angiography [15]. …”
Section: Methodsmentioning
confidence: 99%
“…Among these patients, 90% (n=246) were accrued prospectively as part of NIH protocols utilizing CMR and echo for CAD associated remodeling (NIH 1R01HL128278-01, K23 HL102249-01) [14], and 10% were accrued via a retrospective registry of patients with chronic obstructive CAD as verified by invasive angiography [15]. …”
Section: Methodsmentioning
confidence: 99%
“…DE-CMR was also used to identify NIF, which was defined as localized hyperenhancement in the mid myocardial or epicardial aspect of the basal to mid inter-ventricular septum ( Fig 2 ), in accordance with prior research by our group and others [ 26 28 ]. Cine-CMR was used to assess RV and LV geometry/function: End-diastolic and end-systolic chamber volumes were measured in contiguous short axis images, with results used to calculate EF.…”
Section: Methodsmentioning
confidence: 80%
“…Regarding mechanistic links between NIF, RV DYS and iMR, it should be noted that prior studies have shown NIF to be associated with RV DYS and adverse RV remodeling–including work by our group which has linked NIF to increased RV wall stress [ 26 ]. These data suggest a mechanism whereby iMR results in increased PA pressure, which produces afterload-associated decrements in RV contractile function as well as NIF.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…35 Non-ischemic fibrosis identified on CMR has also been linked to greater degree of RV dilation and afterload and is independently associated with increased mortality in patients with cardiomyopathy. 36, 37 In patients with arrhythmogenic RV Cardiomyopathy (ARVC), CMR indices are critical components of the diagnostic criteria, which includes CMR derived RVEF and end diastolic volume. 38 RV volumetric and functional assessment is important in a wide range of congenital heart disease conditions.…”
Section: Cardiac Mrimentioning
confidence: 99%